Antitumor and anti-angiogenic activity of Ganoderma lucidum polysaccharides peptide - CAO Qi-zhen; LIN Zhi-bin (Acta Pharmacologica Sinica; Vol 25, No 6 (June 2004): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the antitumor and anti-angiogenic activity of Ganoderma lucidum polysaccharides peptide (GLPP). METHODS: Antitumor effect of GLPP was observed in tumor-bearing mice in vivo. At the same time, the effects of GLPP on proliferation of tumor cells and human umbilical cord vascular endothelial cell (HUVEC) were detected by MTT assay in vitro. Subsequently, spleen lymphocytes proliferation of nude mice was stimulated by LPS or ConA. To investigate the anti-angiogenic effect of GLPP, GLPP 80 microg per disc and GLPP-treated serum 10 microL per disc were added to the chick chorioallantoic membrane (CAM) respectively in vivo. RESULTS: GLPP 50, 100, and 200 mg/kg inhibited growth of Sarcoma 180 in BALB/c mice markedly by 35.2 %, 45.2 %, and 61.9 %, respectively. GLPP which was directly added to the cultured medium did not inhibit PG cell proliferation in vitro; but GLPP-treated serum 50, 100, 200 mg/kg potently inhibited PG cell proliferation by 22.5 %, 26.8 %, and 30.3 %, respectively; and reduced the xenograft (human lung carcinoma cell PG) in BALB/c nude mice greatly in vivo by 55.5 %, 46.0 %, and 46.8 %, respectively. Lymphocytes proliferation of nude mice could be stimulated by LPS 5 mg/L but not by ConA 2.5 mg/L, indicating that GLPP could not promote the T lymphocyte proliferation and neutral red phagocytosis of peritoneal macrophages of nude mice. The CAM assay showed that GLPP and GLPP-treated serum had anti-angiogenic effect. GLPP (1, 10, and 100 mg/L) inhibited HUVEC proliferation in vitro with the inhibitory rate of 9.4 %, 15.6 %, and 40.4 %, respectively. CONCLUSION: GLPP has antitumor and anti-angiogenic activity. The anti-angiogenesis of GLPP may be a new mechanism underlying its anti-tumor effects.